KORELASI GENETIK DAN FENOTIP BOBOT SAPIH DAN BOBOT SATU TAHUN KAMBING SABURAI JANTAN DI KECAMATAN SUMBEREJO KABUPATEN TANGGAMUS - Dita Tiara, Akhmad Dakhlan, M. Dima Iqbal, dan Sulastri (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2019)
This research aimed to determine the value of the genetic and phenotypic correlation between weaning weight and yearling weight of male Saburai goat in Sumberejo District, Tanggamus Regency. Ninety male Saburai goats aged one year were used in this study. This research was conducted from May 11th -- July 28th, 2019. The research used primary and secondary data with direct observation in the field and also recording of the livestock from Sumberejo District. The method used was survey method with purposive sampling. Genetic and phenotipic correlation were estimated using halfsib data. Parameters observed were weaning weight and yearling weight. The results showed that the average of weaning weight of male Saburai goats in Sumberejo subdistrict was 17.2 ± 2.7 kg, and the average of yearling weight was 40.8 ± 6.1 kg. Genetic correlation between weaning weight and yearling weight was 0.22 which is categorized as medium positive value, while phenotype correlations between the two traits was low positive of 0.13, and environmental correlations was high positive of 0.33. These results indicated that environmental factors have a big impact on the performance of goats. Keywords: Goat Saburai, Weaning weights, Yearling weight, Genetic correlation, Phenotypic correlation